Canteen Development Innovation and Business Partners Around the Alamtirta Tourism Swimming Pool in Barengkok Village in the Covid Pandemic Era - Dzakwan Akhmad Khan, Sulthan Sami; Firdaus, Muhamad Azis (Jurnal Pengabdian Nusantara, 2023)
This study aims to determine the potential of the Alam Tirta swimming pool tourism object in the Barengkok Village area, Kec. Leuwiliang, by expanding promotion through print media including the distribution of brochures, through electronic media including Instagram, and Tiktok, this report writing uses a combination of qualitative analysis, interviews, document studies, and literature studies. The data obtained were then analyzed qualitatively and presented descriptively. This study aims to find out how important the innovation of facilities at the Alam Tirta Tourism swimming pool is for the convenience of visitors and to make improvements to the canteen facilities and business partners of the Alam Tirta swimming pool and the kiosks provided. Therefore we conclude that the development of innovations for facilities at the Tirta nature tourism swimming pool in Barengkok village is very important for the comfort and interest of visitors and is profitable for business partners around the Tirta nature tourism swimming pool.